Efektivitas Metode Qawaid wa Tarjama dalam Pengajaran Bahasa Arab di Lingkungan Pesantren: Studi Kasus Universitas Annuqayah - Ahmad Faris; Muhammad Hishni Musyarrof (STAI AL-AMIN, 2025)
This study aims to analyze the effectiveness of the Qawaid wa Tarjama (grammar and translation) method in teaching Arabic in pesantren environment, with a case study at Annuqayah University. The Qawaid wa Tarjama method is a traditional approach that focuses on grammar analysis and text translation to build language understanding. This research uses qualitative methods including direct classroom observation, interviews with lecturers and students, and documentation analysis. The results show that this method is effective in improving grammar understanding and enriching student vocabulary. However, the main weakness is the lack of oral communication skills development. The conclusion shows that the Qawaid wa Tarjama method remains relevant in the pesantren context, but needs to be combined with other more communicative methods to achieve more balanced and comprehensive Arabic language learning.